A. Gerd – the initiator of the investigation principle in the methods of teaching of natural sciences - Bernotas , V. (Psichologija, 1972)
The author gives a brief estimation of the standard of teaching in the times of A. Gerd, finding it very low. Wordy-dogmatic methods of teaching predominating then did not satisfy the pedagogue and he insisted upon organizing the process of teaching in such a way that pupils master the matter actively, carrying out some kind of independent investigations. The author analyses those works by A. Gerd in which the pedagogue gives methodical references on the developing of independence of pupils as well as on the carrying out of experiments, observations, excursions and practical work during the lessons of natural sciences in primary school. On the ground of the analysed works the author states that the initiator of the works dealing with independent investigations of pupils in the czarist Russia was A. Gerd. The article also deals with the appreciation of the works by A. Gerd.
Keywords: Gerd; teaching of natural sciences; history of pedagogy